A novel Sugarcane bacilliform virus promoter confers gene expression preferentially in the vascular bundle and storage parenchyma of the sugarcane culm - Gao, San-Ji (Biotechnol Biofuels, 2017)
BACKGROUND: Saccharum species such as sugarcane and energy cane are key players in the expanding bioeconomy for sugars, bioenergy, and production of high-value proteins. Genomic tools such as culm-regulated promoters would be of great value in terms of improving biomass characteristics through enhanced carbon metabolism for sugar accumulation and/or fiber content for biofuel feedstock. Unlike the situation in dicots, monocot promoters currently used are limited and mostly derived from highly expressed constitutive plant genes and viruses. In this study, a novel promoter region of Sugarcane bacilliform virus (SCBV; genus Badnavirus, family Caulimoviridae), SCBV21 was cloned and mapped by deletion analysis and functionally characterized transiently in monocot and dicot species and stably in sugarcane. RESULTS: In silico analysis of SCBV21 [1816 base pair (bp)] identified two putative promoter regions (PPR1 and PPR2) with transcription start sites (TSS1 and TSS2) and two TATA-boxes (TATAAAT and ATATAA), and several vascular-specific and regulatory elements. Deletion analysis revealed that the 710 bp region spanning PPR2 (with TSS2 and ATATAA) at the 3′ end of SCBV21 retained the full promoter activity in both dicots and monocots, as shown by transient expression of the enhanced yellow fluorescent protein (EYFP) gene. In sugarcane young leaf segments, SCBV21 directed a 1.8- and 2.4-fold higher transient EYFP expression than the common maize ubiquitin 1 (Ubi1) and Cauliflower mosaic virus 35S promoters, respectively. In transgenic sugarcane, SCBV21 conferred a preferential expression of the β-glucuronidase (GUS) gene in leaves and culms and specifically in the culm storage parenchyma surrounding the vascular bundle and in vascular phloem cells. Among the transgenic events and tissues characterized in this study, the SCBV21 promoter frequently produced higher GUS activity than the Ubi1 or 35S promoters in a manner that was not obviously correlated with the transgene copy number. CONCLUSIONS: The newly developed plant viral SCBV21 promoter is distinct from the few existing SCBV promoters in its sequence and expression pattern. The potential of SCBV21 as a tissue-regulated promoter with a strong activity in the culm vascular bundle and its storage parenchyma makes it useful in sugarcane engineering for improved carbon metabolism, increased bioenergy production, and enhanced stress tolerance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0850-9) contains supplementary material, which is available to authorized users.